Cultural Familiarity, Foreign Language Speaking Skill, and Foreign Language Anxiety: The Case of Indonesian EFL Learners. (16th April 2022) - Diep, Le Thi Ngoc; Zainal, Anna Gustina; Hassan, Isyaku; Sunarti,; Al-Sudani, Ahmed Qassem Ali Sharhan; Assefa, Yalalem
Abstract : Since cultural aspects of language learning are not incorporated in some EFL materials and textbooks, this study can be important to investigate the impacts of using cultural-based instruction on developing the speaking skill of Indonesian EFL learners. In addition, this research tried to examine the effects of using cultural-based instruction on foreign language anxiety of Indonesian EFL learners. To reach these aims, the Oxford Quick Placement Test (OQPT) was given to 83 EFL learners, and 50 of them were selected for the target sample of the current investigation. The selected respondents were then randomly divided into two equal experimental and control groups. Afterward, the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire was given to both groups. After providing the stated questionnaire, both groups were pretested by a speaking test. After that, the experimental group was instructed by applying a cultural-based instruction, while the control group received a noncultural-based education. After the instruction ended, the FLCAS questionnaire and the posttest of speaking were given to the respondents to determine the effects of the cultural-based instruction on their speaking skills and foreign language anxiety. The collected data were analyzed by using independent samples and paired sample t -tests. The results revealed that the experimental group had better performances than the control group on the speaking and anxiety posttests. Finally, based on the results, some conclusions and implications were suggested.